Obsession Radical Islam's war against the West - Kopping, Wayne; Shore, Raphael; Halperin, Brett; Trinity Home Entertainment (Firm) ([Westlake Village, CA] : Trinity Home Entertainment, 2007)
"Obsession is a film about the threat of Radical Islam to Western civilization. Using unique footage from Arab television, it reveals an "insider's view" of the hatred the Radicals are teaching, their incitement of global jihad, and their goal of world domination. The film also traces the parallels between the Nazi movement of World War II, the Radicals of today, and the Western world's response to both threats."--Container.
DVD.
Closed-captioned.
Narration by Wayne Kopping ; featuring interviews with Martin Gilbert, Robert Wistrich, Khaleel Mohammed, Daniel Pipes, Alan Dershowitz.
Originally released in 2006.
"Winner best feature film 2005 Liberty Film Festival"--Cover.
Keywords: Islamic fundamentalism; Anti-Americanism -- Islamic countries; September 11 Terrorist Attacks, 2001.; War on Terrorism, 2001-; Islamic countries -- Relations -- Western countries; Documentary films; Video recordings for the hearing impaired